The Secret Poison Plot Adolf Hofrichter and the Austro-Hungarian General Staff - John E. Fahey (Journal on European History of Law, 2011)
The Austro-Hungarian Empire's military justice system, like much in the Empire, adapted slowly to changing times. First Lieutenant Adolf Hofrichter's 1909 poisoning of a member of the Army's General Staff, and his subsiquent investigation and trial, illustrate the weaknesses of the Austro-Hungarian court marshal system and its' perception in broader society. The Viennese press's suggestions and complaints about Hofrichter's court marshal, show the need for adaptation and change. The press also illustrate the role of the military within the broader criminal justice system of the fin-de-siecle Austro-Hungarian Empire.